Shoot Multiplication of Pure-line Hom-Kradang-Nga Rice through Callus Formation - Wamaedeesa, Raheema; Kanjanawattanawong, Supanath (Princess of Naradhiwas University Journal, 2019)
This study aims to investigate the effect of suitable quantity of sugar and plant growth regulator on growth and development of Hom-kradang-nga rice seed. Hom-kradang-nga rice seeds were grown on MS medium added 0.5 mg/l 2,4-D and different concentration of table sugar. The result showed that percentage of callus formation was highest (95.31%) when cultured on MS medium with 20 g/l table sugar followed by cultured on MS medium with 10 g/l table sugar (92.18%). MS medium without table sugar gave lowest percentage of callus formation (56.25%).It was found that callus diameter was significant difference (P?0.01). Diameteraverage of callus was highest when cultured on MS medium with 20 g/ltable sugar (0.54 cm). Moreover, calliwere culture on MS medium added 0.5 1 1.5 2 and2.5 mg/l BAin order to examine shoot production and proliferation. The consequence result showed that different concentration of BA influenced on length of shoot and leaf (P ?0.05). MS medium added 2.5 mg/l table sugar gave highest average length of shoot and leaf whereas those concentrations of BA did not show significant difference of shoot and leaf number. Additionally, for shoot proliferation, it was found that all BA concentration did not show significant difference of shoot number average.